Pistes pour une économie morale du sentiment d’injustice parmi les jeunes des quartiers populaires urbains - Éric Marlière (L’Année du Maghreb)
This article proposes to study from a research field the question of the feeling of injustice among young people living in urban neighborhoods. It is thus a question of going back on our old works by proposing a reflection around concepts like that of frustration, of «denied subjectivities», of «politicity» or even of moral economy. To better apprehend the political, social and symbolic stakes which are at the origin of a sense of injustice conveyed by a large number of young people met in the popular districts whatever the origin, the trajectory or the social status, we opted for the notion of moral economy. Indeed, this notion could make it possible to better understand the context in which the sometimes harsh discourses of these young people develop, insofar as the moral economy in a dialectical understanding envisages the springs of action starting from anger and despair. which in fact masks a moral aspiration to justice and citizenship.